Persistent Placoid Maculopathy: Prognosis Factors and Functional Outcomes. (2nd October 2020) - Gascon, Pierre; Matonti, Frederic; Beylerian, Marie; Feldman, Audrey; Comet, Alban; Donnadieu, Benjamin; Loria, Olivier; Denis, Daniele; Kodjikian, Laurent; Mathis, Thibaud
ABSTRACT: Purpose : To identify prognosis factors and functional outcomes of persistent placoid maculopathy (PPM). Methods : We collected personal PPM cases and combined them with the data from the literature. Results : 68 eyes of 37 patients with PPM were analyzed, including six new cases. Twenty-six patients were men (70%) with a mean age of 51.8 years old. The mean initial visual acuity (VA) was 0.52 LogMar ± 0.55 for a mean final VA of 0.49 LogMar ± 0.51. Risk factors for poor VA included: initial VA less than 0.2 LogMar ( p < .0001), cardiovascular risk factor ( p = .008), autoimmune-related and/or systemic pro-inflammatory conditions ( p = .003), choroidal neovascularization ( p = .001), macular atrophy ( p = .03) and absence of systemic corticosteroid treatment ( p = .03). Conclusion : PPM is a choroidal inflammation. Identifying prognosis factors may help to guide treatment and follow-up. We showed that anti-inflammatory drugs, and anti-VEGF injections in cases of choroidal neovascularization, may lead to better outcomes.